Co-creating interactive dining experiences via interconnected and interoperable smart technology. Issue 1 (2nd January 2022) - Leung, Rosanna; Loo, Poh Theng
ABSTRACT: Dining is an essential part of daily life, and the business of any restaurant is to satisfy its customers by co-creating positive dining experiences on every occasion and at every stage in the process. This paper proposed an interconnected and interoperable smart service network to co-create interactive post-pandemic dining experiences that are beneficial to both the customers and restaurant operators by broadcasting personalised location-based promotional messages aggregated from external contextual information collected via sensors attuned to customer dining habits; shape expectations via ambient, sensory information, and images; interact with customers and assist their dining choices by artificial intelligence recommendation systems; and can cook and deliver meals by automated robotic technologies. The theoretical contribution of this paper focuses on developing a smart dining experience framework which optimises the interaction among smart technology, service staff, restaurant managers, customers, and their collective experience. Restaurant managers' awareness and integration of smart technologies and smart services can enhance the overall customer dining experiences and post-dining feedback for continuous real-time improvement.